Cross-Kingdom DNA Methylation Dynamics: Comparative Mechanisms of 5mC/6mA Regulation and Their Implications in Epigenetic Disorders - Liu, Yu; Wang, Ying; Bao, Dapeng; Chen, Hongyu; Gong, Ming; Sun, Shujing; Zou, Gen (Biology (Basel, Switzerland), 2025)
DNA methylation, a cornerstone of epigenetic regulation, governs critical biological processes including transcriptional modulation, genomic imprinting, and transposon suppression through chromatin architecture remodeling. Recent advances have revealed that aberrant methylation patterns—characterized by spatial-temporal dysregulation and stochastic molecular noise—serve as key drivers of diverse pathological conditions, from oncogenesis to neurodegenerative disorders. However, the field faces dual challenges: (1) current understanding remains fragmented due to the inherent spatiotemporal heterogeneity of methylation landscapes across tissues and developmental stages, and (2) mechanistic insights into non-canonical methylation pathways (particularly 6mA) in non-mammalian systems are conspicuously underdeveloped. This review systematically synthesizes the evolutionary-conserved versus species-specific features of 5-methylcytosine (5mC) and N6-methyladenine (6mA) regulatory networks across three biological kingdoms. Through comparative analysis of methylation/demethylation enzymatic cascades (DNMTs/TETs in mammals, CMTs/ROS1 in plants, and DIM-2/DNMTA in fungi), we propose a unified framework for targeting methylation-associated diseases through precision epigenome editing, while identifying critical knowledge gaps in fungal methylome engineering that demand urgent investigation.